2020
DOI: 10.4103/cjp.cjp_84_19
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Aerobic Exercise on Serum Irisin, Adropin, and Cholesterol Levels in the Winter Season

Abstract: The aim of this study is to investigate the acute and chronic effects of aerobic training performed indoors and outdoors on irisin, adropin, and cholesterol levels in winter. Thirty-two healthy males participated in this study. Participants were divided into two groups: outdoor group (n = 16) and indoor group (n = 16). They then performed 40-min aerobic running exercises 4 days/week for 18 weeks. The outdoor group trained at −5°C–5°C environmental temperature, while the indoor group trained at 21°C–25°C. Blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
0
26
0
2
Order By: Relevance
“…It has been well documented that exercise exerts significant physiological adaptations that improve cardiometabolic health. A single bout of aerobic exercise, at approximately 60-80% maximal heart rate for up to 90 minutes, did not elicit a significant alteration in adropin (24,42,165). Furthermore, seven days of exercise training, 1 hour/day at 60% heart rate reserve, was not sufficient to impact adropin concentrations (138).…”
Section: Exercise and Adropinmentioning
confidence: 84%
See 2 more Smart Citations
“…It has been well documented that exercise exerts significant physiological adaptations that improve cardiometabolic health. A single bout of aerobic exercise, at approximately 60-80% maximal heart rate for up to 90 minutes, did not elicit a significant alteration in adropin (24,42,165). Furthermore, seven days of exercise training, 1 hour/day at 60% heart rate reserve, was not sufficient to impact adropin concentrations (138).…”
Section: Exercise and Adropinmentioning
confidence: 84%
“…In response to the exercise interventions, adropin concentrations significantly increased by ~1-1.5ng/ml (14,15,24). However, Ozbay et al (42) did not find a difference in adropin concentrations with acute exercise or after 18 weeks of aerobic training in young healthy males.…”
Section: Exercise-induced Effects On Adropinmentioning
confidence: 91%
See 1 more Smart Citation
“…High-intensity interval training increased irisin in young, healthy males [41,60] and healthy young adults [43], military aerobic training [48] increased irisin blood levels in young, healthy males and one study with a single group design found a significant increase in irisin in young females after treadmill exercise [37]. On the other hand, cycle ergometer-sprint training, consecutive training [77] as well as indoor running [64] led to a decrease of irisin blood levels in young, healthy males, and the same effect was found after basketball training in healthy children [39] or after taekwondo training in obese children [70]. A decrease in irisin blood levels was also found after high-intensity interval training [56], CrossFit training [59], resistance training, and concurrent training [72] in healthy young females as well as after a structured group fitness program in pregnant females [75].…”
Section: Summary Of Main Results and Interpretationsmentioning
confidence: 99%
“…It has been reported that circulating irisin concentrations of young healthy adults increase significantly 30 min after an acute exercise (Huh et al, 2012). Furthermore, a single 40 min of aerobic running can induce minimal increase of serum irisin in both hot (21~25°C) and cold (−5~5°C) environment (Ozbay et al, 2020). Data from animal studies have found that the concentrations of serum irisin increase significantly in hyperthyroidism and hypothyroidism rats after forced swimming with 5% of the weight-bearing body weight for 100 min (Samy et al, 2015).…”
Section: Regulation Of Irisin By Exercise Acute Exercise Increases Circulating Irisin Concentrationmentioning
confidence: 99%